2020
DOI: 10.1002/chem.202000348
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Oxidations in a Cofacial Copper(II) Porphyrin Dimer: Through‐Space Spin‐Coupling and Interplay between Metal and Radical Spins

Abstract: Abstractcis and trans‐copper(II) porphyrin dimers have been synthesized, in which two CuII porphyrin macrocycles are bridged through a rigid ethene linker for possible through‐space and through‐bond spin‐couplings between the paramagnetic CuII centers. It has been found that the two macrocycles come closer after 1 e− oxidation, however, they move far apart upon further 1 e− oxidation leading to transformation of the cis to the trans isomer. Detailed investigations are performed here on the interactions between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 127 publications
0
6
0
Order By: Relevance
“…Homo- and heterometallic species that have metallophilic interactions between closed-electron-shell atoms and ions (d 10 or s 2 systems) become a topical area of research and attracted considerable interest owing to their unique chemical bonding, structure, reactivity, and photophysical properties. Generally, two or more closed-shell cations are expected to repel each other, but recent experimental and theoretical studies provide enough evidence for the attractive interactions arising out of dispersive forces magnified by relativistic effects for heavy elements. The strength of such interactions has been compared to that of hydrogen bonding and is clearly sufficient to confer interesting structural and physical properties such as polychromism, luminescence, electrical conductivity, and so on. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Homo- and heterometallic species that have metallophilic interactions between closed-electron-shell atoms and ions (d 10 or s 2 systems) become a topical area of research and attracted considerable interest owing to their unique chemical bonding, structure, reactivity, and photophysical properties. Generally, two or more closed-shell cations are expected to repel each other, but recent experimental and theoretical studies provide enough evidence for the attractive interactions arising out of dispersive forces magnified by relativistic effects for heavy elements. The strength of such interactions has been compared to that of hydrogen bonding and is clearly sufficient to confer interesting structural and physical properties such as polychromism, luminescence, electrical conductivity, and so on. …”
mentioning
confidence: 99%
“…Urea-bridged porphyrin dimer is highly flexible and can easily interconvert between three conformations, i.e., cis–cis , trans–cis , and trans–trans , based on the solvent polarity (Scheme S2). Two porphyrin rings should be in a cofacial arrangement but slipped, which is the geometric requirement for strong π–π interaction. , Although the porphyrin dimer is highly flexible, two strong mercurophilic interactions only bring two porphyrin macrocycles on the exact top of each other with fully eclipsed geometry which are, otherwise, highly unstable.…”
mentioning
confidence: 99%
“…The reason behind the different magnetic behaviors can be found from the Cu–Cu distances between the two radical spins, that is, ∼2.7 Å in conformations A and C allowing a ferromagnetic coupling, versus 4.1 Å in conformation B, in which the cores are well separated (Figure ). According to the experimental ferromagnetic exchange couplings for the three complexes ( J Cu–Cu , Table ), the most probable structure of C1 – C3 would fit with conformation A, which shows the lowest Gibbs energy and J Cu–Cu values (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, the experimental and computational results for this series of complexes demonstrated that the tripyrrindione ligand is not affected by degradation problems common to The crystal structures of Pd II , Ni II , and Cu II tripyrrindiones revealed discrete π-radical dimers with head-to-tail orientation and interplanar π−π distances ranging from 3.19 to 3.45 Å (Figure 4A). 37 These cofacial interactions are reminiscent of those in porphyrin radical dimers 40,41 of interest for applications in artificial photosynthetic and electron/energy transfer systems. 42,43 In this context, we sought to investigate the dimerization equilibria of tripyrrindione radicals in solution.…”
Section: Synthesis and Redox Chemistry Of Tripyrrindione Complexesmentioning
confidence: 99%